On direct variational formulations for second order evolutionary equations - Budochkina, Svetlana Aleksandrovna; Savchin, Vladimir Mikhailovich (Eurasian Mathematical Journal, 2012)
The existence of direct variational formulations for a wide class of second order evolutionary equations is investigated.